KEABSAHAN DAN KEKUATAN HUKUM KONTRAK ANJAK PIUTANG YANG DI BUAT SECARA ELEKTRONIK: Validity And Legal Force Of Factoring Contracts Made Electronically - Fariha, Gina Afina Ulfa (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2025)
This study discusses the validity and legal force of electronic factoring agreements from the perspective of civil law and positive law in Indonesia. In the digital era, the use of electronic documents and signatures has become increasingly common as a means of efficiency in business transactions, including factoring agreements. However, issues arise regarding the validity and evidentiary value of agreements made electronically. This study aims to analyze how the Indonesian legal system, through Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) and its amendments, as well as the Civil Code (KUHPerdata), provides a legal basis for the validity of these electronic agreements. The research method used is normative juridical with a statutory and conceptual approach. The results of the analysis indicate that electronic factoring agreements have legal validity if they meet the requirements for a valid agreement as stipulated in Article 1320 of the Civil Code, namely the existence of an agreement, the capacity of the parties, a specific object, and a lawful cause. Meanwhile, its legal force is supported by the provisions of Article 5 and Article 11 of the ITE Law which recognizes electronic documents and signatures as valid evidence. Thus, factoring agreements made electronically have the same legal standing as conventional agreements, as long as they are made with due regard for the principle of prudence, the authenticity of the parties' identities, and the security of the electronic system used. This research emphasizes the importance of adapting civil law to legal certainty and protection for parties in electronic contract transactions